An Intervention Program Based on Plant Surrogates as Alternatives to the Use of Southern Ground-Hornbills in Cultural Practices - Coetzee, Hendri; Nell, Werner; van Rensburg, Leon (Ethnobotany Research and Applications, 2014)
The Southern Ground-Hornbill (SGH) (Bucorvus leadbeateri Vigors, 1825) is a globally threatened bird. The least studied and addressed threat facing the SGH is its use in traditional African cultural practices. This study aimed to develop and refine an intervention program based on the use of plant surrogates as alternatives to the use of SGHs in such practices. Following a grounded-action research approach, a preliminary week-long program was developed and implemented among a group of 10 traditional healers from South Africa. Feedback from the participants was analyzed qualitatively and used to refine the program. The participants identified several readily available and culturally congruent plant surrogates that could be used as alternatives to the SGH. Whilst the program requires additional refinement and implementation across the bird’s range, preliminary results indicate that the use of non-threatened plant species as surrogates for the SGH, as well as for similarly threatened species, holds promise as a rapid, cost-effective, and culturally sensitive conservation intervention.